My name is Anton : a novel - Hyde, Catherine Ryan (Lake Union Publishing, 2020)
"It's 1965, and life has taken a turn for eighteen-year-old Anton Addison-Rice a year after his brother died in a tragic accident, Anton is still wounded - physically and emotionally. Alone for the holidays, he catches a glimpse of his neighbor Edith across the street one evening and realizes that she's in danger. Anton is determined to help Edith leave her abusive marriage. Frightened and fifteen years Anton's senior, Edith is slow to trust. But when she needs a safe place to stay, she lets down her guard, and over the course of ten days an unlikely friendship grows. As Anton falls hopelessly and selflessly in love, Edith fears both her husband finding her and Anton getting hurt. She must disappear without telling anyone where she's going - even Anton. If keeping Edith safe means letting her go, Anton will say goodbye forever. Or so he believes. What would happen, though, if one day their paths should cross again?"--Provided by publisher.